The Impact of Nonequilibrium Flow on the Structure of Turbulence Over River Dunes. Issue 9 (19th September 2018) - Unsworth, C. A.; Parsons, D. R.; Hardy, R. J.; Reesink, A. J. H.; Best, J. L.; Ashworth, P. J.; Keevil, G. M.
Abstract: Most past experimental investigations of flow over river dunes have focused on conditions that match semiempirical flow‐depth scaling laws, yet such equilibrium conditions are of limited value because they rarely occur in natural channels. This paper quantifies the structure of mean and turbulent flow over fixed 2‐D laboratory dunes across a range of nonequilibrium conditions within the dune flow regime. The flow field was quantified using 2‐D particle imaging velocimetry for 12 conditions, including flows that are too deep, too shallow, too fast, or too slow for the size of the fixed dunes. The results demonstrate major departures in the patterns of the mean flow and structure of turbulence when compared to dunes formed under equilibrium flow conditions. The length of flow reattachment scales linearly with the ratio of mean depth‐averaged streamwise velocity to shear velocity at the dune crest ( U ¯ c / u c * ), which provides a new predictive measure for flow reattachment length. Depth‐averaged vertical velocities at the dune crest ( V ¯ c ) show a parabolic relationship with U ¯ c, peaking at U ¯ c ~0.60 m/s, which matches the relationship of dune aspect ratio with transport stage present in mobile bed conditions. The spatial location of the turbulent wake was found to vary with flow depth and velocity, with lower U ¯ c and greater flow depths causing the wake to rise toward the free surface. Deeper flows are likely to show less flow convergence over the crests of dunes due to reduced interaction of turbulence with the free surface, resulting in a reduction of transport stage. Plain Language Summary: This piece of research expands our description of how rivers flow over dunes on a river bed. Most of the scientific communities' research to date has used unnaturally steady conditions to measure how water moves over dunes. Yet these flow conditions are not strictly true to the variety of conditions nature produces, most importantly during floods. This research is the first detailed description of a wide range of flow states over dunes and changes our present understanding of the structure of flow over dunes in rivers. Consequently, the scientific community will be able to use this new information to better model and simulate how rivers work, how they flood, and how they transport sediment toward the world's deltas. Key Points: Flow reattachment length over dunes can be predicted with one equation over a wide range of nonequilibrium conditions Transport stage and the magnitude of flow upwelling at a dune crest are used to understand the variety of dune shapes that exists In nonequilibrium conditions the spatial location and intensity of turbulence deviate considerably from previous research at equilibrium